ICT Enabled Disease Diagnosis, Treatment and Management—A Holistic Cost-Effective Approach Through Data Management and Analysis in UAE and India - Kumar M V, Manoj; Patil, Jagadish; Shastry, K. Aditya; Darshan, Shiva; Sastry, Nanda Kumar Bidare; Moonesar, Immanuel Azaad; Atalla, Shadi; Almuraqab, Nasser; Rao, Ananth (Frontiers in Artificial Intelligence, 2022)
Purpose: This concept paper proposes an electronic approach to good health, responds to the relevant challenges identified in the United Nations (UN) 2030 Agenda Sustainable Development Goals (SDG) 3; 8 ; and 9 , as well as the National Health Policy of India (NHP-India) and the Ministry of Health Policy of UAE (MHP-UAE). These two country policies stress the need for a digital health technology ecosystem. The concept has 3 Goals. Goal 1 focuses on using innovative, patient-centered, clinician and patient-facing digital healthcare technologies to improve patient experiences and healthcare services delivery at the Point of Care (POC). Goal 2 focuses on exploring the understanding of how the use of patient-centered digital healthcare technologies impacts patient outcomes, experiences, and healthcare services delivery at the POC. Goal 3 focuses on applying advanced analytics to improve quality at the POC. Design Approach: The Concept's Goal 1 is proposed through designing services such as Virtual consultations (VC), Tele-pharmacy (TP), Virtual storage space (VSS), and VCom. The Concept's Goals 2 and 3 are proposed by designing Data Management & Analytical (DMA) Architecture. In DMA, individual researchers and health care professionals in India and UAE would be able to uncover and harness the Primary Health Care (PHC) and POC data into practical insights. Impact: The concept is proposed to augment the PHC and POC systems with ICT based interventions to enable cost-effective healthcare delivery and potentially change the health outcome and result in better health for patients. The conceptual design is open and flexible, and it allows users to access a wide range of digital materials. Uniqueness: The conceptual framework provides patients, including their data, access to specialist doctors from around the globe via the VHC; Improved health due to compliance to holistic disease treatment plans and access to scientific health information; and Reduction in Out of pocket expenses to patients. Originality/Value: This is the first study to conceptualize Disease Diagnosis, Treatment & Management in UAE and India, fast-emerging economies in the backdrop of UN's 2030 SDG 3, 8, and 9 targets to be achieved through digitization of primary health care services.